Results in semi-E-convex functions - Benhadid, Ayache (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
The concept of convexity and its various generalizations is important for quantitative and qualitative studies in operations research or applied mathematics. Recently, E-convex sets and functions were introduced with important implications across numerous branches of mathematics. By relaxing the definition of convex sets and functions, a new concept of semi-EE-convex functions was introduced, and its properties are discussed. It has been demonstrated that if a function f:M→Rf:M→R is semi-EE-convex on an EE-convex set M⊂RnM⊂Rn then, f(E(x))≤f(x)f(E(x))≤f(x) for each x∈Mx∈M. This article discusses the inverse of this proposition and presents some results for convex functions.